Inteligência emocional e gestão de conflitos na sala de aula: interfaces razão-emoção a partir de relatos e reflexões docentes - Marques, Vanessa da Silva (Universidade do Vale do Rio dos Sinos, 2016)
This paper presents a participating research-action, counting upon the participation of nine teachers working at Young’s Apprentice Program (YAP). Among the references used we point out Miguel Angel Zabalza as a support to the usage of the class diary and Daniel Goleman with the Emotional Inteligence theory. The teachers have participated in a Teachers Development Program (PRODED), where they have been introduced to the class diary and invited to register the conflicts experienced in the classroom. The class diary (CD) is the main research instrument of the present study, which had as its main objective, analyze the teaching practice and the emotional intelligence when facing conflictive situations, starting from a process of formation – investigation through the use of the class diary. The data analysis was done based on Discursive Textual Analysis (DTA) starting from four categories, being: classroom conflicts, reactions when facing conflictive situations, emotions and reflections about the practice. The analysis of the classroom conflicts and reactions when facing conflictive situations revealed the teachers are presenting paralisation, imediatist actions and ponderate actions to manage situations related to the students which not participate on the activities, disrespect the rules and are verbally aggressive. The analysis of the categories emotions and reflections about the practice, pointed out that among the several emotions mentioned by the teachers, fear, sadness and anger were the primary emotions they manifested in the conflictive situations. Those situations were related to the student´s behavior, violence, life risk, i.e., situations where the teachers felt impotent, incompetent, hopeless in changing student´s behavior and also because they can´t control and avoid some situations. The category reflection about the practice discussed about the teacher´s reports related to their reflexive process, difficulties and fears and about their competences, satisfaction and challenges of this profession. The results of this study, shown the reflection about the practice, starting from the use of the CD contribute for the identification of the emotions and the re-reading about the teacher’s actions and reactions facing conflictive situations. Finally, we point out the contribution of the psychology for Educational Management field, since the study of the emotions and human behavior reveal as being of a big contribution to support the teachers, proposing the exercise about practice reflection. Consequently, the reflection about the practice also stimulates the teachers self knowledge and the development the emotional intelligence for managing the classroom conflicts.
Keywords: Situações conflitivas; Diário de aula; Inteligência emocional; Reflexão sobre a prática; Conflictive situations; Class diary; Emotional intelligence; Reflection about the practice; ACCNPQ::Ciências Humanas::Educação